IL-10 na competência oocitária após a refrigeração de ovários e de complexos cumulus-oócitos de majoritariamente Bos taurus indicus - Oliveira, Gil Neves Pinto de (Universidade Federal de São Carlos, 2025)
The use of ovaries from slaughterhouses is a common practice for research involving early animal development. However, the transportation time and handling of these ovaries prior to culture can negatively affect oocyte competence. Interleukin-10 (IL-10) is an anti-inflammatory cytokine with regulatory potential in the embryonic environment and blastocyst development. This study aimed to evaluate whether IL-10 promotes oocyte competence after refrigeration of ovaries or cumulus-oocyte complexes (COCs) at 4°C. The effect of IL-10 was evaluated in COCs from ovaries refrigerated at 4°C or maintained at 30°C during transport to the laboratory and refrigerated at 4°C for 3 h prior to in vitro maturation (IVM). Nuclear maturation was assessed by monitoring the rate of first polar body extrusion and cumulus cell expansion. DNA fragmentation of oocytes and cumulus cells (CCs) were also investigated by the TUNEL technique, and cytoplasmic maturation was assessed by evaluating the distribution of cortical granules. For statistical analysis, the data obtained were subjected to analysis of variance (ANOVA) followed by Tukey's test. A significance level of 5% was adopted. No effect (P>0.05) of IL-10 and refrigeration on the expansion and DNA fragmentation of CCs was identified. However, the polar body extrusion rate of the control group of refrigerated ovaries (23.3±3.0%) was lower (P<0.05) than the other groups (41.3±6.3, 48.0±3.1, and 39.6±4.4%, respectively for control treatments at 30 °C, IL-10 at 30 °C, and refrigerated IL-10). In the groups at 30 °C with IL-10, in both experiments, lower percentages of fragmented DNA were obtained in the oocytes (8.3%: 2/24 and 20.7%: 6/29). Furthermore, the oocytes from the groups refrigerated with the addition of IL-10, both for prevention and reversal purposes, presented a percentage of apoptosis (32.1%: 9/28 and 31.3%: 10/32) very similar to the control group at 30 °C (32.0%: 8/25). It is concluded that IL-10 was effective in rescuing the nuclear maturation of oocytes when subjected to refrigeration, however, without noticeable effects on cumulus cells and cytoplasmic granules.
IL-10 in oocyte competence after cooling of ovaries and cumulus-oocyte complexes of majorly Bos taurus indicus
Keywords: Interleucina-10; Maturação in vitro; Oócitos; Produção in vitro de embriões; Interleukin-10; In vitro maturation; Oocytes; In vitro embryo production; CIENCIAS BIOLOGICAS